2019
DOI: 10.1021/jacs.8b12596
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanistic Basis for Anaerobic Ergothioneine Biosynthesis

Abstract: Ergothioneine is an emergent factor in cellular redox biochemistry in humans and pathogenic bacteria. Broad consensus has formed around the idea that ergothioneine protects cells against reactive oxygen species. The recent discovery that anaerobic microorganisms make the same metabolite using oxygen-independent chemistry, indicates that ergothioneine also plays physiological roles under anoxic conditions. In this report we describe the crystal structure of the anaerobic ergothioneine biosynthetic enzyme EanB f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…An excellent phylogenetic analysis is given by Jones et al (60) . In more recent work, it has been suggested that ERG was probably first biosynthesised by anaerobes using a slightly different route that converts hercynine directly to ERG (98)(99)(100) , and that was later repurposed. Three-dimensional structures are known for a number of the relevant enzymes, including mycobacterial EgtB (101) for example, PDB 4XBE, EgtC (102) for example, PDB 4ZFJ, EgtD (103)(104)(105) for example, PDB 4PIM, and Neurospora crassa early G1 transcript 2 (egt2) which is like egtE (106) for example, PDB 5UTS.…”
Section: Biosynthesis and Phylogenetic Distributionmentioning
confidence: 99%
“…An excellent phylogenetic analysis is given by Jones et al (60) . In more recent work, it has been suggested that ERG was probably first biosynthesised by anaerobes using a slightly different route that converts hercynine directly to ERG (98)(99)(100) , and that was later repurposed. Three-dimensional structures are known for a number of the relevant enzymes, including mycobacterial EgtB (101) for example, PDB 4XBE, EgtC (102) for example, PDB 4ZFJ, EgtD (103)(104)(105) for example, PDB 4PIM, and Neurospora crassa early G1 transcript 2 (egt2) which is like egtE (106) for example, PDB 5UTS.…”
Section: Biosynthesis and Phylogenetic Distributionmentioning
confidence: 99%
“…Comparing the bacterial and fungal pathway, it is important to note that the utilization of glutamate in the ergothioneine biosynthesis pathway also requires ATP. Recently, enzymes for the anaerobic production of ergothioneine were found in Chlorobium limicola (Burn et al, 2017), where sulfur is directly transferred to the imidazole ring of hercynine to form ergothioneine (Leisinger et al, 2019). However, it is suggested that the anaerobic C-S bond formation is less efficient than it's aerobic counterpart (Burn et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…By analogy to related sulfur transferases, [18] we initially thought that a pyridoxal 5′‐phosphate (PLP) dependent cysteine desulfurase is required to extract and transfer sulfur atoms from free cysteine to EanB [16a] . Upon further analysis we realized that soluble polysulfides generated from partially oxidized hydrogen disulfide can also serve as the primary sulfur donor [16b, 19] . This finding has been confirmed recently by an independent study [20] …”
Section: Figurementioning
confidence: 81%